Effects of whole-body vibration training on cognitive function: A systematic review - Wen, Jiayi; Leng, Lu; Hu, Min; Hou, Xiaohui; Huang, Junhao (Frontiers in Human Neuroscience, 2023)
Background: Whole-body vibration training is a novel training method that stimulates the human neuromuscular system by the use of vibration, the frequency and amplitude of which are controlled, thereby inducing adaptive changes in the body. Whole-body vibration training is widely used as a clinical prevention and rehabilitation tool in physical medicine and neuro-rehabilitation as a clinical prevention and rehabilitation tool. Objectives: The aim of the present study was to review the effects of whole-body vibration on cognitive function, provide an evidence-based foundation for future research on whole-body vibration training, and promote additional popularization and use of the methodology in clinical practice. Methods: A systematic review of articles extracted from the following six databases was conducted: PubMed, Web of Science, China National Knowledge Infrastructure, Embase, Cochrane and Scopus. A literature search was performed on articles in which the effects of whole-body vibration on cognitive function were evaluated. Results: Initially, a total of 340 studies were initially identified, among which 18 articles that satisfied the inclusion criteria were selected for inclusion in the systematic review. Participants were allocated into two groups: patients with cognitive impairment and healthy individuals. The results demonstrated that whole-body vibration was both positive and ineffective in its influence on cognitive function. Conclusions: The majority of studies suggested that whole-body vibration may be a useful strategy for the management of cognitive impairment and should be considered for inclusion in rehabilitation programs. However, the impact of whole-body vibration on cognition requires additional, larger, and adequately powered studies.